Predictive value of tip-apex distance and calcar-referenced tip-apex distance for cut-out in 398 femoral intertrochanteric fractures treated in a private practice with dynamic intramedullary nailing - Barra, Amariel E.; Barrios, Carlos (Frontiers in Surgery, 2024)
Introduction Cut-out, a biomechanical complication, is one of the most common causes of internal fixation failure of trochanteric hip fractures. The tip-apex distance (TAD) and the calcar-referenced tip-apex distance (CalTAD) have been suggested as the radiographic parameters that most predict the risk of cut-out. The purpose of this study was to check whether these two factors could predict implant cut-out in a series 398 of intertrochanteric hip fractures, treated by dynamic intramedullary nailing with the Trigen Intertan short nail. Methods We reviewed 398 consecutive intertrochanteric fractures included in a prospective study and treated in a single private hospital by the same surgeon. The radiographic parameters were obtained from anteroposterior (AP) and axial hip plain radiographs before surgery, immediately postoperatively, and every 3 weeks after surgery until 3 months postoperatively, and every month until the 6-month follow-up. The concept of medial cortex support (MCS) was also analyzed as a criterion for evaluating the quality of fracture reduction. Results The overall cut-out rate was 2.3% (9/398). The significant parameters in the univariate analysis were AO fracture type, quality of fracture reduction (p = 0.02), TAD (p < 0.001), CalTAD (p = 0.001), and quality of reduction. No statistically significant relationships were observed between the occurrence of cut-out and sex, age, fracture side, and American Society of Anesthesiologists type. Varus collapse and cut-out were only found in cases of negative MCS (22.2% and 77.8%, respectively). Multivariate analysis showed that only TAD showed an independent significant relationship to cut-out (p < 0.001). In this study, CalTAD has no predictive value in the multivariable analysis. Conclusions Our findings differed from those in previous reported studies suggesting that CalTAD is the best predictor of cut-out. According to our data, careful optimal reduction ensuring stable fixation with TAD >25 mm reduced the occurrence of cut-out after dynamic intramedullary nailing of intertrochanteric fractures.